Previous gestational diabetes history is associated with impaired coronary flow reserve. (3rd October 2015) - Caliskan, Mustafa; Turan, Yasar; Caliskan, Zuhal; Gullu, Hakan; Ciftci, Faika Ceylan; Avci, Enver; Duran, Cevdet; Kostek, Osman; Telci Caklili, Ozge; Koca, Harun; Kulaksizoglu, Mustafa
Abstract: Background Gestational diabetes mellitus (GDM) is a prediabetic state that is known to increase the risk of cardiovascular diseases. We have investigated coronary flow velocity reserve (CFVR) and epicardial fat thickness (EFT), and left ventricular diastolic function in patients with a history of previous GDM (p-GDM). Methods Ninety-three women with GDM history and 95 healthy women without GDM history were recruited. We used transthoracic Doppler echocardiography to assess CFVR, EFT, and left ventricular diastolic function. Insulin resistance of each subject was assessed with homeostasis model assessment insulin resistance (HOMA-IR). Hemoglobin A1c and high-sensitivity C-reactive protein (hsCRP) were also measured in all patients. Results CFVR values were significantly lower (2.34 ± 0.39 versus 2.80 ± 0.24, p < 0.001) and EFT values were significantly higher in patients with p-GDM than the control group (5.5 ± 1.3 versus 4.3 ± 1.1, p < 0.001). E/E' ratio (7.21 ± 1.77 versus 6.53 ± 1.38, p = 0.003), hemoglobin A1c (5.2 ± 0.4 and 5.0 ± 0.3, p = 0.001), HOMA-IR (2.8 ± 1.4 versus 1.7 ± 0.9, p = 0.04), and hsCRP levels were significantly higher in the p-GDM group than the control group. Multivariate analysis revealed that gestational diabetes history is independently associated with CFVR. Conclusion Women with a GDM history may be at more risk regarding coronary microvascular dysfunction compared to the healthy ones. Key Messages: What is already known about this subject? Impairment of CFVR reflects coronary microvascular dysfunction and has been shown to be an early manifestation of atherosclerosis and coronary artery disease. Several studies have shown an association between p-GDM and atherosclerosis by measuring intima-media thickness. What are new findings? This preliminary study on coronary microvascular function of patients with p-GDM revealed that CFVR is significantly impaired in p-GDM patients. Although the number of patients included in this study is limited, these results suggest that impaired CFVR may be an early manifestation of coronary vascular involvement in patients with p-GDM. How might it impact on clinical practice in the foreseeable future? In patients with p-GDM, the presence of impaired CFVR should render the clinician aware of the development of coronary artery disease.